Effects of functional supports on efficiency and stability of atomically dispersed noble-metal electrocatalysts - Kim, Seongbeen; Park, Jinkyu; Hwang, Jongkook; Lee, Jinwoo (EnergyChem, 2021)
Atomically dispersed metal catalysts (ADCs), particularly of noble metal, have unique catalytic properties such as maximized atom efficiency, high catalytic activity, and superior selectivity. In ADCs, the metal centers are in intimate contact with the support, hence, the support significantly affects the catalytic behavior of the ADCs by participating in reactions, either directly or indirectly. Therefore, for electrocatalytic reactions, thorough understanding of the function of the supports is required in designing effective ADCs with superior activity and stability. In this review, we summarize and discuss the functions of supports in several synthesis strategies and electrocatalytic reactions of atomically dispersed noble-metal catalysts. We outline various synthesis strategies, and identify a need for a suitable design of the support to stabilize the atom-dimension metal structure. Furthermore, we describe (electro)catalysis of ADCs, with focus on support-derived factors that affect the catalytic performance of the ADCs, such as strong metal-support interaction (SMSI), geometric effects of atom-dimension structure, local environment near metal centers, and chemical properties of supports. Finally, we identify current challenges and future prospects of functional supports in ADCs.
Keywords: Atomically dispersed catalyst; Dispersed metals; Electrocatalytic reactions; Ensemble; Functional support; Metal catalyst; Metal centres; Single-atoms; Strong metal-support interaction; ]+ catalyst; Atomically dispersed catalyst; Electrocatalytic reactions; Ensemble; Functional support; Noble metal; Single atom; Strong metal-support interaction